2018
DOI: 10.3390/su10051489
|View full text |Cite
|
Sign up to set email alerts
|

Stress Regulation, Physical Activity, and Perseverance in Spanish Teenagers with Perfectionist Trends

Abstract: Stress as an emotional response with adaptive function can obstruct both academic performance and psychosocial and physiological functioning when it is recurrent, persistent, and intense. Individual characteristics and regular physical activity produce differences in ways of coping with pressure situations, stressing the necessity of teenagers handling them in an effective way for their psychological adjustment and well-being. The purpose of this investigation was to identify how the frequency of physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
(47 reference statements)
1
6
0
1
Order By: Relevance
“…Regarding the measurement of the precompetitive moment, we can also find an inverse correlation between academic performance and demotivation. Both cases could coincide with the opinion of Hernandez et al [62] on the decrease in academic performance based on a physiological and psychological obstruction on the part of a submission to situations of continued stress. However, there are multiple studies on achievement motivation on school moments themselves on academic performance [35][36][37].…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the measurement of the precompetitive moment, we can also find an inverse correlation between academic performance and demotivation. Both cases could coincide with the opinion of Hernandez et al [62] on the decrease in academic performance based on a physiological and psychological obstruction on the part of a submission to situations of continued stress. However, there are multiple studies on achievement motivation on school moments themselves on academic performance [35][36][37].…”
Section: Discussionsupporting
confidence: 82%
“…However, this study finds that stress has no significant impact on academic performance, and only anxiety presents a weak predictive effect on academic performance among all negative emotions, which is quite different from previous studies and verifies H2. Past research has shown that high levels of anxiety and depression have a negative effect on students' academic performance, since they can affect memory as well as concentration [12,13,17], and students with more academic stress are more likely to perform poorly on exams [14]. Achievement goals and academic self-efficacy are not controlled in these studies, so the conclusions may be biased, and negative emotions may not directly affect academic performance.…”
Section: Discussionmentioning
confidence: 96%
“…Aronen et al reported that anxiety and depression can affect memory as well as concentration, which leads to poor academic performance [15]. Depression is found to have a significant mediation effect between physical activity and academic performance [16], and stress is also proven to obstruct both academic performance and psychosocial and physiological functioning as an emotional response with adaptive function [17]. Although anxiety, depression, and stress are all classified as negative emotions, their impacts on academic performance are not entirely consistent in previous studies.…”
Section: Negative Emotionsmentioning
confidence: 99%
“…In the same way, various previous studies have been conducted, which have taken the same approach. These include studies conducted in References [38,39,40,41,42].…”
Section: Discussionmentioning
confidence: 99%